Advancement of microdosimetric kinetic model in heavy-ion radiotherapy. (October 2020) - Inaniwa, T
Abstract: To date, more than 11, 000 cancer patients have been treated with therapeutic carbon-ion beams at the National Institute of Radiological Sciences (NIRS). In the treatment planning system, the biological effectiveness of the therapeutic carbon-ion beams has been predicted based on the microdosimetric kinetic (MK) model. The MK model has a variety of applications. For instance, it can be used to predict the biological effectiveness of therapeutic carbon-ion beams under protracted irradiations as well as under hypoxic conditions. Recently, we have updated the MK model to a stochastic microdosimetric kinetic (SMK) model for a new research project about hypo-fractionated multi-ion radiotherapy, referred to as a "Quantum Scalpel". This report overviews advancement of the MK model in heavy-ion radiotherapy.